Vertical dynamic response of a pile embedded in radially inhomogeneous soil based on fictitious soil pile model. Issue 132 (May 2020) - Cai, Yanyan; Liu, Zehan; Li, Tianbin; Yu, Jin; Wang, Ning
Abstract: The vertical dynamic response of a pile embedded in radially inhomogeneous soil is investigated while allowing for the vertical wave effect of soil. For most engineering applications, the soil adjacent to pile may be hardened or softened due to the construction disturbance effect of pile, leading to the radial inhomogeneity of soil which has a significant influence on the vibration characteristics of pile. To consider this problem, this paper introduced the vertical shear complex stiffness transfer model to simulate the radial inhomogeneity of the surrounding soil and underlying soil of pile. Then, the governing equations of pile-soil system subjected to vertical dynamic loading are established based on the fictitious soil pile model. By means of Laplace transfer method, vertical shear complex stiffness transfer method and impedance function transfer method, the analytical solution of the vertical dynamic impedance of pile head is derived in the frequency domain. The present solution is verified by comparing it with existing solution. Based on the present solution, a parametric study is conducted to study the influence of the construction disturbance effect of pile surrounding soil and underlying soil on the vertical dynamic response of pile head. The results show that, even if the surrounding soil of pile is hardened or softened within a very small range, the construction disturbance effect still has a remarkable influence on the vertical dynamic response of pile head. Highlights: The present solutions can take both the inhomogeneity of pile surrounding soil and pile end soil into account. The vertical shear complex stiffness transfer method is used to simulate the inhomogeneity of soil in the radial direction. The disturbance influences the vertical dynamic response of pile head largely even if the surrounding soil deforms a little.